Measuring the Level of Pedagogical Discontentment Among Jordanian Science and Vocational Student Teachers - Qablan, Ahmad M.; Abu Tineh, AbdAullah M.; Khasawneh, Samer A.; Al Omari, Aieman Ahmad (جامعة الكويت - مجلس النشر العلمي, 2010)
هدفت هذه الدراسة إلى قياس مستوى عدم القناعة التدريسية لدى طلاب التربية العملية في مساقي العلوم والتربية المهنية في الجامعة الهاشمية. وقد تكونت أداة الدراسة من ٣٨ فقرة أجاب عن أسئلتها ٧٤ طالبا وطالبة ممن شاركوا في برنامج التربية العملية للعام الدراسي 2005/ 2006 م وقد أشارت نتائج الدراسة إلى أن طلبة التربية العملية في مساقي العلوم والتربية المهنية عبروا عن درجة عالية من مستوى عدم القناعة التدريسية، إلا أن ذلك المستوى من عدم القناعة التدريسية كان الأعلى لدى طلبة مساق التربية المهنية. كما أشارت نتائج الدراسة إلى عدم وجود فروقات ذات دلالة إحصائية تعزى إلى الجنس والمعدل التراكمي بين افراد عينة الدراسة. وأخيرا، توصلت نتائج الدراسة إلى ان النقص في المعرفة المتعلقة بطرائق التدريس، وعدم وجود برنامج متخصص في إعداد معلمي التربية المهنية، ونقص الدعم والتشجيع من مديري المدراس المتعاونة ومعلميها كانت من الأسباب الرئيسة لعدم القناعة التدريسية للطلبة المشاركين في الدراسة. The purpose of this study was to measure levels of pedagogical discontentment (PD) among science and vocational internship teachers at the Hashemite University in Jordan. A 38-item valid and reliable instrument named the Pedagogical Discontentment Questionnaire (PDQ) was used to collect data from a sample of 74 preservice teachers during the academic year 2005/2006. Results indicated that science and vocational preservice teachers expressed high levels of PD during their teaching experience, where vocational teachers demonstrated a higher level of PD compared with science teachers. Moreover, non-significant differences attributed to gender and GPA were found. Finally, reasons for that high level of PD were the lack of having sufficient pedagogical content knowledge, lack of well-established vocational curricula, and lack of support and encouragement from collaborative teachers and school adminis-trators.
Keywords: التعليم الجامعي -- التربية العملية -- الرضا الوظيفي -- الجامعة الهاشمية -- معلمو العلوم -- معلمو التربية المهنية